Ações afirmativas na sociedade de classes: um estudo sobre o ingresso do negro na Unioeste (2014-2016) - Furtado, Claudio Oliveira (2018)
This paper addresses the affirmative actions in Brazil aimed at the black population, within the class society, taking into account the challenges, perspectives of access in undergraduate courses, with reference to Unioeste. It is a bibliographical and documentary research whose exposition is organized in three chapters. The theoretical-methodological method that guided this work is given by the analysis of the society of classes, understanding how the blacks are inserted in its interior. We recognize the Negro not as a social group apart, but as a constituent part of the whole working class. The implementation of the reserve system of vacancies/ quotas in public universities has been presented as a promoter of the democratization of access to opportunities in higher education. Despite the legislation and new public policies implemented in the last decades, such initiatives are still insufficient in the face of the reality of inequalities and social exclusion, since such policy is the subject of many discussions and controversies reducing the subject to a simplistic view, against or in favor Studying social practices, we try to get out of this polarization to understand the interpretations about blacks in the History of Education. From this historiographical analysis we find that they have been inferior in traditional history. When analyzing the black, in the work and in the school education from the beginning of the Brazilian colonization, we verified some paradoxes, like its reduced participation in the formal education, and its later attempt of inclusion. Despite being the majority of the Brazilian population, the black presence in the Brazilian Higher Education is very low in relation to the whites, mainly in the Unioeste campuses. After several centuries of the discovery of Brazil, the socioeconomic differences between whites and blacks remain. With the approval of Law nº. 12,711, of August 29, 2012, which allocates 50% of vacancies to self-declared candidates, blacks, brown or indigenous people, it has resumed debates on affirmative action, not only at an educational level, but also at a social level. The process of implementing this Law points to the need to problematize the racial question within the universities. Based on this perspective, this research questions whether the policy of reserving vacancies / quotas really contributes to the democratization of access and permanence in higher education.